2006
DOI: 10.1534/genetics.106.057836
|View full text |Cite
|
Sign up to set email alerts
|

The F-Box Protein Dia2 Overcomes Replication Impedance to Promote Genome Stability in Saccharomyces cerevisiae

Abstract: The maintenance of DNA replication fork stability under conditions of DNA damage and at natural replication pause sites is essential for genome stability. Here, we describe a novel role for the F-box protein Dia2 in promoting genome stability in the budding yeast Saccharomyces cerevisiae. Like most other F-box proteins, Dia2 forms a Skp1-Cdc53/Cullin-F-box (SCF) E3 ubiquitin-ligase complex. Systematic analysis of genetic interactions between dia2D and 4400 viable gene deletion mutants revealed synthetic lethal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
90
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(97 citation statements)
references
References 108 publications
(158 reference statements)
7
90
0
Order By: Relevance
“…F-box proteins provide target specificity to the Skp1-Cullin-F-box (SCF)-complex-mediated ubiquitination of proteins that are destined for degradation by the proteasome. The nucleolar F-box protein Dia2 interacts physically or genetically with 15 ribosome assembly factors (Ho et al 2002;Blake et al 2006;Pan et al 2006), and its partners Cdc53 and Hrt1 bind three additional ones (Ho et al 2002;Davierwala et al 2005). In addition, Dia2 interacts with the cullin Rtt101 and Mms1.…”
Section: Post-translational Modifications Of Ribosomal Proteins and Amentioning
confidence: 99%
“…F-box proteins provide target specificity to the Skp1-Cullin-F-box (SCF)-complex-mediated ubiquitination of proteins that are destined for degradation by the proteasome. The nucleolar F-box protein Dia2 interacts physically or genetically with 15 ribosome assembly factors (Ho et al 2002;Blake et al 2006;Pan et al 2006), and its partners Cdc53 and Hrt1 bind three additional ones (Ho et al 2002;Davierwala et al 2005). In addition, Dia2 interacts with the cullin Rtt101 and Mms1.…”
Section: Post-translational Modifications Of Ribosomal Proteins and Amentioning
confidence: 99%
“…We and others have shown that dia2⌬ cells exhibit synthetic growth phenotypes on normal media in combination with checkpoint mutants (4,17,28,43). We tested a series of these double mutants for their sensitivity to HU, which induces replication stress.…”
Section: Vol 30 2010 Regulation Of the F-box Protein Dia2 165mentioning
confidence: 99%
“…The dia2⌬ mutant is hypersensitive to DNA damage, exhibits chromosome loss and rearrangement, and accumulates DNA damage foci (4,17,28). Dia2 is a bona fide F-box protein in that it assembles with Skp1, Cdc53, and Rbx1 into a functional SCF ubiquitin ligase complex (15,(17)(18)(19).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…org/supplemental/). To date, there are 79 MAD1 synthetic lethal interactions identified in S. cerevisiae (Wang and Burke 1995;Hardwick et al 1999;Krogan et al 2004;Lee and Spencer 2004;Tong et al 2004;Measday et al 2005;Montpetit et al 2005;Blake et al 2006;Daniel et al 2006;Pan et al 2006). We used reciprocal best blastp (Altschul et al 1997) analysis to identify putative C. elegans orthologs for 37 of these 79 genes (supplemental Table 1).…”
mentioning
confidence: 99%